High-dose N-acetylcysteine therapy in the treatment of pneumonia (Perioperaciina Medicina, 2021)
The article presents modern data on the use of N-acetylcysteine in the treatment of infectious diseases of the respiratory tract in the practice of a physician. Its antioxidant, mucolytic, anti-inflammatory, pulmoprotective and antitoxic properties are described. The emphasis is placed on the antioxidant properties of N-acetylcysteine, which are expressed when used in high doses of 1200 mg/day or more. There is a review of the literature on the use of high doses of N-acetylcysteine in the treatment of pneumonia, cystic fibrosis, COPD, ARDS. The effect of N-acetylcysteine on individual risk factors for prolonged pneumonia is analyzed. Given the epidemiological situation around the world, the antioxidant properties of N-acetylcysteine in the treatment of pneumonia, including complicated COVID-19, are relevant and require further study.
Keywords: COVID-19; N-acetylcysteine; pneumonia